THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING HISTORY AND STUNTING INCIDENCE IN CHILDREN AGED 7-36 MONTHS IN THE KERA AREA OF PESANTREN I HEALTH CENTER, KEDIRI CITY - Rahma Kusuma Dewi; Lindha Sri Kusumawati; Mayasari Putri Ardela; Siti Aminah; Erna Zuli Oktavia; Dwi Ayu Lestari (Journal for Quality in Women's Health, 2025)
Stunting results from nutritional deficiencies during pregnancy and early childhood, affecting physical growth and brain development. Maternal, child, and environmental factors contribute to stunting, which can impair physical, cognitive, and motor development, impacting a child's quality of life. This study analyzes the relationship between risk factors and stunting in children aged 24–59 months in Puskesmas Semen, Kediri Regency, in 2023. Using a correlational approach, 189 randomly selected children were analyzed with the Chi-Square test. Low maternal education increased stunting risk (RR 0.3, p < 0.05), while higher education levels were not significant. Non-exclusive breastfeeding (RR 2.9), low birth weight (RR 2.6), short birth length (RR 2.2), and maternal height <150 cm (RR 1.6) were key risk factors. Preventing stunting requires improving maternal education, promoting exclusive breastfeeding, and monitoring birth weight, birth length, and maternal height during pregnancy